Elevated 20-HETE in metabolic syndrome regulates arterial stiffness and systolic hypertension via MMP12 activation. (April 2018) - Soler, Amanda; Hunter, Ian; Joseph, Gregory; Hutcheson, Rebecca; Hutcheson, Brenda; Yang, Jenny; Zhang, Frank Fan; Joshi, Sachindra Raj; Bradford, Chastity; Gotlinger, Katherine H.; Maniyar, Rachana; Falck, John R.; et al.
Abstract: Arterial stiffness plays a causal role in development of systolic hypertension. 20-hydroxyeicosatetraeonic acid (20-HETE), a cytochrome P450 (CYP450)-derived arachidonic acid metabolite, is known to be elevated in resistance arteries in hypertensive animal models and loosely associated with obesity in humans. However, the role of 20-HETE in the regulation of large artery remodeling in metabolic syndrome has not been investigated. We hypothesized that elevated 20-HETE in metabolic syndrome increases matrix metalloproteinase 12 (MMP12) activation leading to increased degradation of elastin, increased large artery stiffness and increased systolic blood pressure. 20-HETE production was increased ~7 fold in large, conduit arteries of metabolic syndrome (JCR:LA-cp, JCR) vs. normal Sprague-Dawley (SD) rats. This correlated with increased elastin degradation (~7 fold) and decreased arterial compliance (~75% JCR vs. SD). 20-HETE antagonists blocked elastin degradation in JCR rats concomitant with blocking MMP12 activation. 20-HETE antagonists normalized, and MMP12 inhibition (pharmacological and MMP12-shRNA-Lnv) significantly improved (~50% vs. untreated JCR) large artery compliance in JCR rats. 20-HETE antagonists also decreased systolic (182 ± 3 mmHg JCR, 145 ± 3 mmHg JCR + 20-HETE antagonists) but not diastolic blood pressure in JCR rats. Whereas diastolic pressure was fully angiotensin II (Ang II)-dependent, systolic pressure was only partially Ang II-dependent, and large artery stiffness was Ang II-independent. Thus, 20-HETE-dependent regulation of systolic blood pressure may be a unique feature of metabolic syndrome related to high 20-HETE production in large, conduit arteries, which results in increased large artery stiffness and systolic blood pressure. These findings may have implications for management of systolic hypertension in patients with metabolic syndrome. Highlights: 20-HETE regulates large artery remodeling (arterial stiffness) via MMP12 activation and elastin degradation 20-HETE antagonists reverse arterial stiffness and normalize systolic blood pressure in metabolic syndrome Effects of 20-HETE antagonists on arterial stiffness are Ang II-independent; effects on systolic blood pressure are partially Ang II-dependent 20-HETE antagonists may provide viable therapy for treatment of isolated systolic hypertension